(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is one of the current problems of today, in which the idea of healthy upbringing is studied, that living a physically healthy life is the essence of a person’s life, and the issues of forming positive qualities and qualities of a person are highlighted.